Perioperative antithrombotic management of patients who receive direct oral anticoagulants during gastroenterological surgery - Takahisa Fujikawa; Ryo Takahashi; Shigetoshi Naito (Annals of Gastroenterological Surgery, 2020)
Abstract Aim We investigated the effect of perioperative management of direct oral anticoagulants (DOACs) on bleeding and thromboembolic complications during gastroenterological (GE) surgery. Methods A total of 334 patients receiving anticoagulants and undergoing elective GE surgery between 2012 and 2018 were enrolled. The patients were divided into three groups: patients receiving warfarin (WF, n = 231), patients receiving DOACs with heparin bridging (DOAC‐HB, n = 34), and patients receiving DOAC without heparin bridging (DOAC‐NHB, n = 69). Outcome variables were compared between the groups and the risk factors of postoperative bleeding were assessed using logistic multivariate analysis. Results No significant differences were observed in background characteristics between the groups. There were similarities between the groups in surgical blood loss (P = .772) and rate of intraoperative transfusion (P = .952). Thromboembolic complications only occurred in two patients in the WF group (0.9%), and no thromboembolism occurred in the DOAC groups. The incidence of major postoperative bleeding was significantly higher in DOAC‐HB group than in the other groups (14.7% vs 4.8% vs 1.4%, P = .011). Multivariate analysis showed DOAC with heparin bridging to be the most significant risk factor of major postoperative bleeding (odds ratio = 11.60, P = .028). Conclusions Elective GE surgery can be safely performed in patients receiving DOACs without heparin bridging. Perioperative heparin bridging during DOAC interruption is not recommended even for patients undergoing major GE surgery due to increased postoperative bleeding.